Phenobarbital overdose in an eleven-year-old-girl with attempted suicide - V Lily Limantara; Made Widia; Ketut Suwitra; Endah Ardjana (Paediatrica Indonesiana, 2005)
This report describes a patient with life-threat-ening phenobarbital overdose, treated successfullywith hemodialysis, using a high-flux, high-efficiencydialyzer and high blood flow rates. The rapid fall inphenobarbital levels and the dramatic clinical re-sponse noted during the procedure supports thistechnique as an effective therapy in such patients.